2009
DOI: 10.1038/jes.2009.31
|View full text |Cite
|
Sign up to set email alerts
|

TCDD exposure estimation for workers at a New Zealand 2,4,5-T manufacturing facility based on serum sampling data

Abstract: Employment in the manufacture of the herbicide 2,4,5-trichlorophenoxyacetic acid (2,4,5-T) is associated with potential exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) and elevated serum lipid TCDD concentrations can be measured in workers for decades after terminated occupational exposure. As part of an epidemiological study of 1599 workers employed at a facility in New Plymouth, New Zealand that manufactured 2,4,5-T, serum TCDD concentrations measured in blood samples from 346 workers were used with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Full details of the exposure modelling were the subject of an earlier report. 11 The work history records and serum data were used to estimate TCDD dose rates for each job exposure group, and because of the 7-year half-life of TCDD, this informed earlier exposure levels. There were two basic assumptions in the exposure reconstruction model: firstly that exposure for an individual job within a job exposure group could be modelled as a constant, consistent and average exposure rate in nanograms per year.…”
Section: Methodsmentioning
confidence: 99%
“…Full details of the exposure modelling were the subject of an earlier report. 11 The work history records and serum data were used to estimate TCDD dose rates for each job exposure group, and because of the 7-year half-life of TCDD, this informed earlier exposure levels. There were two basic assumptions in the exposure reconstruction model: firstly that exposure for an individual job within a job exposure group could be modelled as a constant, consistent and average exposure rate in nanograms per year.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have indicated that the carcinogenic capacity of TCDD may be due to the interaction between TCDD and the aryl hydrocarbon receptor (AhR). This receptor is implicated in several xenobiotic metabolisms but there is evidence that AhR is able to control other genes, some of which have a pro-oncogenic capacity [182][183][184] . The TCDD is an important AhR agonist and is therefore able to induce and enhance HCC development and diffusion [184] .…”
Section: Dioxins and Dioxin-like Compoundsmentioning
confidence: 99%
“…Oral administration of PCB 126 resulted in a notably higher incidence of HCA and CLC (32,226). The most important epidemiological studies of TCDD carcinogenicity were cohort studies of herbicide producers and users in the US, the Netherlands and Germany, and of the residents of a contaminated area at Seveso, Italy (218,230233). All found an increased risk for lung cancer, soft tissue sarcoma and non-Hodgkin lymphoma, primarily in the more heavily exposed sub-groups (135,218).…”
Section: Resultsmentioning
confidence: 99%
“…TCDD is well known to upregulate the genes encoding the enzymes involved in xenobiotic metabolism, such as CYP1A1 (238). However, increasing data indicates that AhR controls the expression of a variety of genes not associated with xenobiotic metabolism (239,233). In human lymphocytes, TCDD, a potent AhR agonist, markedly increased the frequency of SCEs (234).…”
Section: Resultsmentioning
confidence: 99%